Is the use of two versus one long-acting bronchodilator by patients with COPD associated with a higher risk of acute coronary syndrome in real-world clinical practice? - Rod Jackson; Simon Horsburgh; Jack Dummer; Lianne Parkin; Sheila Williams; David Barson; Katrina Sharples (BMJ Open Respiratory Research)
Background Cardiovascular comorbidity is common among patients with chronic obstructive pulmonary disease (COPD) and there is concern that long-acting bronchodilators (long-acting muscarinic antagonists (LAMAs) and long-acting beta2 agonists (LABAs)) may further increase the risk of acute coronary events. Information about the impact of treatment intensification on acute coronary syndrome (ACS) risk in real-world settings is limited. We undertook a nationwide nested case–control study to estimate the risk of ACS in users of both a LAMA and a LABA relative to users of a LAMA.Methods We used routinely collected national health and pharmaceutical dispensing data to establish a cohort of patients aged >45 years who initiated long-acting bronchodilator therapy for COPD between 1 February 2006 and 30 December 2013. Fatal and non-fatal ACS events during follow-up were identified using hospital discharge and mortality records. For each case we used risk set sampling to randomly select up to 10 controls, matched by date of birth, sex, date of cohort entry (first LAMA and/or LABA dispensing), and COPD severity.Results From the cohort (n=83 417), we identified 5399 ACS cases during 281 292 person-years of follow-up. Compared with current use of LAMA therapy, current use of LAMA and LABA dual therapy was associated with a higher risk of ACS (OR 1.28 (95% CI 1.13 to 1.44)). The OR in an analysis restricted to fatal cases was 1.46 (95% CI 1.12 to 1.91).Conclusion In real-world clinical practice, use of two versus one long-acting bronchodilator by people with COPD is associated with a higher risk of ACS.